Hajj and Umrah Bot: Facilitating Queries by Pilgrims - Syed Adnan, Sharifah Natasya (IRC, 2020)
Hajj and Umrah pilgrims require a fast response answer from an expert during Hajj and Umrah rituals. This project is to develop a Hajj and Umrah bot in facilitating questions from Hajj and Umrah pilgrims to assist them to achieve a labor Hajj. Hajj and Umrah bot will be a platform for the pilgrims to ask any queries related to Hajj and Umrah rituals. This Chatbot can be accessed and found in Telegram. The user just needs to search for the username of the Hajj and Umrah bot and they can start posting questions inside the bot. Next, Hajj and Umrah bot will be implemented using open-source software, which will bring efficiency and flexibility to the system. Using Visual Studio Code as Source Code Editor together with the Telegram bot can help the development of this project. This project will discuss how Hajj can and Umrah pilgrims send questions to the bot without waiting too long for an answer. Several features have been implemented in the chatbot like users can choose questions, add to the group. The purpose of this project is to assist the pilgrims in providing a fast response to question about Hajj and Umrah rituals.